Identification and Genome Characterization of Begomovirus and Satellite Molecules Associated with Lettuce (Lactuca sativa L.) Leaf Curl Disease - Yafei Tang; Mengdan Du; Zhenggang Li; Lin Yu; Guobing Lan; Shanwen Ding; Tahir Farooq; Zifu He; Xiaoman She (Plants)
Lettuce (Lactuca sativa L.) plants showing leaf curl and vein enation symptoms were found in Yunnan province, China. PCR detection with genus-specific primers revealed that symptomatic lettuce plants were infected with Begomovirus. The full-length viral component and satellite molecules were obtained by RCA, restriction enzyme digestion, PCR, cloning and DNA sequencing. A viral component (YN-2023-WJ) and three satellite molecules (YN-2023-WJ-alpha1, YN-2023-WJ-alpha2 and YN-2023-WJ-beta) were obtained from diseased lettuce plants. YN-2023-WJ exhibited the highest nt identity at 97.1% with pepper leaf curl Yunnan virus isolated from cigar plants. YN-2023-WJ-beta displayed the highest nt identity at 93.9% with tomato leaf curl China betasatellite. YN-2023-WJ-alpha1 showed the highest nt identity at 94.7% with ageratum yellow vein alphasatellite. YN-2023-WJ-alpha2 shared the highest nt identity at 75.6% with gossypium mustelinum symptomless alphasatellite and vernonia yellow vein Fujian alphasatellite. Based on the threshold for the classification of Begomovirus, Betasatellite and Alphasatellite, YN-2023-WJ was designated as a new isolate of PepLCYnV, YN-2023-WJ-beta as a new isolate of ToLCCNB and YN-2023-WJ-alpha1 as a new member of AYVA, whereas YN-2023-WJ-alpha2 was identified as a new geminialphasatellite species, for which the name pepper leaf curl Yunnan alphasatellite (PepLCYnA) is proposed. To the best of our knowledge, this is the first report of L. sativa L. infection by PepLCYnV associated with ToLCCNB, AYVA and PepLCYnA, and L. sativa L. is a new host plant of Begomovirus.